Affirmative action and social desirability - Burle, Fernanda Rivera (2020)
Affirmative action policies implemented in public universities in Brazil cover three main groups: public school students, low-income students, and black and indigenous students. Attitudes about affirmative action policy, when measured conventionally in surveys, can be contaminated by the social desirability bias effect. This article seeks to evaluate if attitudes about the different types of affirmative action policies recently adopted in Brazil are subject to the social desirability bias effect, and, if so, what are the determinants of this effect. To measure the social desirability bias effect and its determinants, we conducted a list experiment among 12.490 university students in 2013. The results reveal that attitudes about the three types of affirmative action policies are prone to a social desirability bias effect. We also find evidence that two individual-level determinants (self-interest and prejudice against the target group) and one contextual-level determinant (students’ field of study) explain the social desirability bias effect.